KIF1C and new Huntingtin-interacting protein 1 binding proteins regulate rheumatoid arthritis fibroblast-like synoviocytes’ phenotypes - Laragione, Teresina; Harris, Carolyn; Gulko, Percio S. (Frontiers in Immunology, 2024)
Background: HIP1 is a new arthritis severity gene implicated in the regulation of the invasive properties of rheumatoid arthritis (RA) fibroblast-like synoviocytes (FLS). These invasive properties of FLS strongly correlate with radiographic and histology damage in RA patients and rodent models of arthritis. While HIP1 has several intra-cellular functions, little is known about its binding proteins and identifying them has the potential to expand our understanding of its role the cell invasion and other disease-contributing phenotypes, and potentially identify new targets for therapy. Methods: FLS cell lines from arthritic DA (highly invasive) and from arthritis-protected congenic rats R6 (minimally invasive), which differ in an amino-acid changing HIP1 SNP, were cultured, lysed and proteins immunoprecipitated with an anti-HIP1 antibody. Immunoprecipitates were analyzed by mass spectrometry. Differentially detected (bound) proteins were selected for functional experiments using siRNA knockdown in human RA FLS to examine their effect in cell invasiveness, adhesion, cell migration and proliferation, and immunofluorescence. Results: Proteins detected included a few known HIP1-binding proteins and several new ones. Forty-five proteins differed in levels detected in the DA versus R6 congenic mass spectrometry analyses. Thirty-two of these proteins were knocked-down and studied in vitro, with ten inducing significant changes in RA FLS phenotypes. Specifically, knockdown of five HIP1-binding protein genes (CHMP4BL1, COPE, KIF1C, YWHAG and YWHAH) significantly decreased FLS invasiveness. Knockdown of KIF1C also reduced RA FLS migration. The binding of four selected proteins to human HIP1 was confirmed. KIF1C co-localized with lamellipodia, and its knockdown prevented RA FLS from developing an elongated morphology with thick linearized actin fibers, or to form polarized lamellipodia, all required for cell mobility and invasion. Unlike HIP1, KIF1C knockdown did not affect Rac1 signaling.We have identified new HIP1-binding proteins and demonstrate that ten of them regulate key FLS phenotypes. These HIP1-binding proteins have the potential to become new therapeutic targets, and help better understand the RA FLS pathogenic behavior. KIF1C knockdown recapitulated the morphologic changes previously seen in the absence of HIP1, but did not affect the same cell signaling pathway, suggesting involvement in the regulation of different processes.